EL DESEMPLEO Y SU INFLUENCIA EN LA CALIDAD DE VIDA DE LOS OBREROS QUE ACUDEN AL PARQUE CENTRAL DE LA CIUDAD DE LOJA - Ordoñez Gordillo, Adriana Cecibel (2019)
The present work of the thesis titled UNEMPLOYMENT AND ITS INFLUENCE ON THE QUALITY OF LIFE OF THE WORKERS WHO COME TO THE CENTRAL PARK OF THE CITY OF LOJA, allowed to fulfill the general objective that was established in determining the incidence of unemployment in the quality of life of the workers, to design a proposal for social intervention that will allow the reduction of this problem In addition, the specific objectives facilitated the identification of theories about the object of study, which allowed to know the causes of unemployment and to establish strategies of intervention against the quality of life of the workers. The methodology used in this research was based on a scientific, inductive - deductive, analytical study, which served to explain and provide alternative solutions to the research problem, with the help of basic quantitative and qualitative research instruments and incorporated the scale of (GENCAT). The total population was considered 70 workers in their totality. The main findings that determined the research, significantly affects the quality of life of workers, a factor that affects family members, and generates social problems. Against this background, the importance of the Social Worker is highlighted, through a proposal of social intervention that is directed to the inclusion of the workers in the government programs, with the purpose that they are the generators of change through the training and awareness through an active participation that will help them in their personal growth.